Viscoelastic Testing in the Clinical Management of Subarachnoid Hemorrhage and Intracerebral Hemorrhage - Hvas, Christine Lodberg; Hvas, Anne-Mette (Seminars in Thrombosis and Hemostasis, 2022)
Subarachnoid hemorrhage (SAH) and intracerebral hemorrhage (ICH) are both debilitating and life-threatening incidents calling for immediate action and treatment. This review focuses on the applicability of viscoelastic testing (rotational thromboelastometry or thromboelastography [TEG]) in the management of SAH and ICH. A systematic literature search was performed in PubMed and EMBASE. Studies including patients with SAH or ICH, in which viscoelastic testing was performed, were identified. In total, 24 studies were included for analysis, and further subdivided into studies on SAH patients investigated prior to stenting or coiling (n = 12), ICH patients (n = 8) and studies testing patients undergoing stenting or coiling, or ischemic stroke patients undergoing thrombolysis or thrombectomy and developing ICH as a complication (n = 5). SAH patients had increased clot firmness, and this was associated with a higher degree of early brain injury and higher Hunt-Hess score. SAH patients with delayed cerebral ischemia had higher clot firmness than patients not developing delayed cerebral ischemia. ICH patients showed accelerated clot formation and increased clot firmness in comparison to healthy controls. Patients with hematoma expansion had longer clot initiation and lower platelet aggregation than patients with no hematoma expansion. During stent procedures for SAH, adjustment of antiplatelet therapy according to TEG platelet mapping did not change prevalence of major bleeding, thromboembolic events, or functional outcome. Viscoelastic testing prior to thrombolysis showed conflicting results in predicting ICH as complication. In conclusion, viscoelastic testing suggests hypercoagulation following SAH and ICH. Further investigation of the predictive value of increased clot firmness in SAH seems relevant. In ICH, the prediction of hematoma expansion and ICH as a complication to thrombolysis might be clinically relevant.
Keywords: thromboelastography; subarachnoid hemorrhage; intracerebral hemorrhage; blood coagulation